Effect of DSPE-PEG on compound action potential, injury potential and ion concentration following compression in ex vivo spinal cord. (4th May 2016) - Wang, Aihua; Huo, Xiaolin; Zhang, Guanghao; Wang, Xiaochen; Zhang, Cheng; Wu, Changzhe; Rong, Wei; Xu, Jing; Song, Tao
Highlights: Gap potential variance after injury describe ex vivo injury potential. DSPE-PEG restore CAP at a much lower concentration than PEG. Application of DSPE-PEG after SCI hardly change intracellular ions concentration. The CAP restoring effect of DSPE-PEG relies on membrane resealing. Abstract: It has been shown that polyethylene glycol (PEG) can reseal membrane disruption on the spinal cord, but only high concentrations of PEG have been shown to have this effect. Therefore, the effect of PEG is somewhat limited, and it is necessary to investigate a new approach to repair spinal cord injury. This study assesses the ability of 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine- N -[methoxy(poly (ethylene glycol)) 2000] (DSPE-PEG) to recover physiological function and attenuate the injury-induced influx of extracellular ions in ex vivo spinal cord injury. Isolated spinal cords were subjected to compression injury and treated with PEG or DSPE-PEG immediately after injury. The compound action potential (CAP) was recorded before and after injury to assess the functional recovery. Furthermore, injury potential, the difference in gap potentials before and after compression, and the concentration of intracellular ions were used to evaluate the effect of DSPE-PEG on reducing ion influx. Data showed that the injury potential and ion concentration of the untreated, PEG and DSPE-PEG group, without significant difference among them, are remarkably higher than those of the intact group. Moreover, the CAP recovery of the DSPE-PEG and PEG treated spinal cords was significantly greater than that of the untreated spinal cords. The level of CAP recovery in the DSPE-PEG and PEG treated groups was the same, but the concentration of DSPE-PEG used was much lower than the concentration of PEG. These results suggest that instant application of DSPE-PEG could effectively repair functional disturbance in SCI at a much lower concentration than PEG.